Vertical Profiles of 226Ra and 228Ra Activity Concentrations in the Western Subarctic Gyre of the Pacific Ocean - Tazoe, Hirofumi; Obata, Hajime; Hara, Takuya; Inoue, Mutsuo; Tanaka, Takahiro; Nishioka, Jun (Frontiers in Marine Science, 2022)
The vertical activity concentration distributions of the radium isotopes, 226Ra and 228Ra, which are useful as radiotracers, were obtained for the first time in the western Subarctic Pacific Gyre (WSAG). It was possible to detect short-lived 228Ra present from the surface to 400 m depth by analyzing large seawater samples. Low 228Ra and high 226Ra activity concentrations in the surface layer in the WSAG were strongly influenced by upwelled deeper water with nutrients. The activity concentration distribution of 226Ra especially was in good agreement with the silicate concentration distribution, which was consistent with previous reported findings. These distributions were uniform from the surface to 100 m of the dichothermal layer due to vertical mixing in winter. 228Ra activity concentration decreased with water depth below the pycnocline and reached the undetectable level at 600 m which was within the oxygen minimum layer. Estimations of vertical fluxes of 228Ra and nitrate according to 228Ra decay indicated that the vertical transport by eddy diffusion was a minor process for the 228Ra and nitrate fluxes, and lateral transport mainly affected 228Ra in the intermediate warm water, that is, the mesothermal layer below the main pycnocline. Vertical mixing or submarine underground water and lateral transport to the WSAG could yield this 228Ra in the intermediate depth.